Insight into catalyst deactivation mechanism and suppression techniques in thermocatalytic deoxygenation of bio-oil over zeolites - Alaba, P.A.; Sani, Y.M.; Mohammed, I.Y.; Daud, W.M.A.W. (De Gruyter, 2016)
The economic viability of the thermocatalytic upgrade of biomass-derived oxygenates is facing the challenge of low-quality products. This is because of leaching of active species, coking, and concomitant catalyst deactivation. These cumulate into the loss of catalytic activity with time on stream (TOS), which causes low degree of deoxygenation. Thus, this article reviews recent advances aimed at alleviating these setbacks to make the process viable for industrial scale-up. To understand the concept of catalyst deactivation and to offer solutions, the review scrutinized the deactivation mechanism diligently. The review also analyzes deactivation-suppression techniques such as nanocrystal zeolite cracking, hydrogen spilt-over (HSO) species, and composite catalysts (hybrid, hierarchical mesoporous zeolite, modified zeolites, and catalytic cracking deposition of silane). Interestingly, these deactivation-suppression techniques enhance catalytic properties mostly by reducing the signal strength of strong acid sites and increasing hydrothermal stability. Further, the approaches improve catalytic activity, selectivity, and TOS stability because of the lower formation of coke precursors such as polynuclear aromatics. However, despite these many advances, the need for further investigations to achieve excellent catalytic activity for industrial scale-up persists.